Higher Ictal EEG Amplitude Predicts Greater PANSS Improvement in Schizophrenia Patients Undergoing Electroconvulsive Therapy: A Two-Group Analytical Study in Surakarta, Indonesia - Cindy Berlian Sulaeman; Debree Septiawan; Adriesti Herdaetha (HM Publisher, 2026)
Background: Schizophrenia frequently responds incompletely to antipsychotics, and electroconvulsive therapy (ECT) remains an important somatic augmentation for severe or treatment-resistant disease; however, the neurophysiological determinants of ECT response are shifting from seizure duration toward ictal electroencephalographic (EEG) quality, of which peak ictal amplitude is a putative but under-tested marker. Methods: This analytical two-group study at RSJD dr. Arif Zainuddin, a tertiary psychiatric hospital in Surakarta, Central Java, Indonesia, enrolled 36 consecutively sampled inpatients (18 per group) with DSM-5-TR/ICD-11-confirmed schizophrenia undergoing ECT, reported per STROBE. Peak ictal EEG amplitude was dichotomised at 1000 µV; the Positive and Negative Syndrome Scale (PANSS), applied by trained raters using the validated Indonesian adaptation, was measured before and after the ECT course. Analyses included paired and independent t-tests, correlation, receiver-operating-characteristic (ROC) analysis, and multivariable linear and penalised logistic regression. Results: Both groups improved (both paired p<0.001), but the ≥1000 µV group achieved markedly greater total-PANSS reduction (34.7±9.2 vs 23.2±8.5 points; mean difference 11.5, 95% CI 5.5–17.5; t(34)=3.90; p=0.0004; Cohen d=1.30) and higher ≥30% response (72.2% vs 16.7%). Continuous amplitude correlated with PANSS reduction (r=0.73, p<0.001), the adjusted odds ratio for response was 4.85 (95% CI 1.56–15.06), and amplitude discriminated responders well (AUC 0.88; Youden cut-off 1093 µV; sensitivity 81%, specificity 90%). Conclusion: Higher ictal EEG amplitude independently predicts greater symptomatic improvement in schizophrenia, supporting routine intra-procedural amplitude monitoring to optimise therapeutic seizure quality, particularly in resource-constrained psychiatric practice.